Regaining Candidacy for Heart Transplantation after Robotic Assisted Laparoscopic Radical Prostatectomy in Left Ventricular Assist Device Patient. (9th October 2012) - Khemees, Tariq A.; Shabsigh, Ahmad
Abstract : Several factors may highlight the relevance of prostate cancer to the pre-heart-transplant population. First, the expansion in candidate selection criteria led to increased number of men over the age of fifty to be considered for heart transplantation. With the introduction of left ventricular assist device (LVAD) therapy, waiting-list mortality has dramatically declined over the past decade. Additionally, transplant candidates are diligently screened for preexisting neoplasm while on the waiting list. Taken together, screening-detected prostate cancer may increasingly be diagnosed in patients on the waiting list. If discovered, it will pose unique challenge to clinicians as to date there has been no universally accepted management guideline. We report a case of LVAD-treated heart transplant candidate diagnosed with prostate cancer while on the waiting list. Patient screening demonstrated PSA elevation which prompted prostate biopsy. Low-risk clinically localized prostate cancer was confirmed and led to removal of patient from transplant list. When counseled regarding management of his cancer, the patient elected to undergo radical prostatectomy in a hope to regain candidacy for heart transplantation. Despite being of high surgical risk, multidisciplinary team approach led to successful management of prostate cancer and the patient eventually received heart transplant one year following prostatectomy.